Answer:
(2,-2)
Step-by-step explanation:
y=-4x+6
y=3x-8
plug the y's in for each other to get:
-4x+6=3x-8 <----- solve from there
+8 +8
-4x+14=3x
+4x +4x
14=7x
/7 /7
x=2
now plug the x in to get y (in any problem)
y=3(2)-8
y=6-8
y=-2
<em>(2,-2)</em>
5 is to 7 as is to 49 is to 51
There are no real solutions
Alright, let's factor this to get the answer.
3k^2-10k+7
To find the factors, we want to think "What will add up to -10, and multiply to (+)7?"
Because the leading coefficient is 3, we know that we can take one factor of 7 and multiply it by 3.
Thus, this factors to
(3k-7)(k-1)
(if you FOIL it it should come out to be the original equation)
From this, set both of those [(3k-7) and (k-1)] equal to zero and solve
3k-7=0
3k=7
/3
k=7/3
or
k=1